Ethanol vapor is an efficient inducer of the alc gene expression system in model and crop plant species - Sonnewald, Uwe; et al. (Plant Physiology, 2002)
We have demonstrated that low concentrations of ethanol vapor efficiently induce the alc gene expression system in tobacco (Nicotiana tabacum cv Samsun NN), potato (Solanum tuberosum cv Solara), and oilseed rape (Brassica napus cv Westar). For many situations, this may be the preferred method of induction because it avoids direct application of comparatively high concentrations of an ethanol solution. Although induction was seen with less than 0.4 muM ethanol vapor, maximal induction of the chloramphenicol acetyl transferase gene was achieved after 48 h in leaves of tobacco plants enclosed with 4.5 muM ethanol vapor. In the absence of ethanol, there is no detectable gene expression. Treatment of potato tubers with ethanol vapor results in uniform beta-glucoronidase (GUS) expression. Vapor treatment of a single oilseed rape leaf resulted in induction of GUS in the treated leaf only and C-14-ethanol labeling in tobacco confirmed that the inducer was not translocated. In contrast, enclosure of the roots aerial parts, or whole plant with ethanol vapor resulted in induction of GUS activity in leaves and roots. The data reported here broaden the utility of the alc system for research and crop biotechnology.